Analisis Pencapaian Ground Time Pesawat Airbus A350-900 Maskapai Singapore Airlines Terhadap Kinerja Petugas Ramp Handling di Bandar Udara Internasional Juanda Surabaya - Eva Qoudria; Suprapti Suprapti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Ground time is one of the important things in handling aircraft while in the apron area and Ramp handling officers are responsible for block on to block off activities and play an important role in improving service functions in the apron area. Ground time that does not comply with company standards can affect flight schedules and operational costs for an airline. This research aims to analyze the ground time achievements of the Airbus A350-900 aircraft on the performance of ramp handling officers. The method used in this research is a quantitative approach with data collection techniques, namely observation and interviews. The data analysis technique uses SPSS 25 which includes descriptive analysis by processing primary data in the form of ground time records for the Airbus A350-900 aircraft for two months which has been adjusted to secondary data, namely company documents to determine the average (mean) ground time each month.Based on the results of descriptive analysis to find out the average ground time, the results obtained in August were 55.53 minutes and in September it was 55.93 minutes, meaning that in general the ground time was still achieved and the performance of the ramp handling officers was very good because they reached the ground time on time. . If ground time is looked at based on the daily schedule, there are still several delays caused by several factors, namely delays in the arrival of planes from the origin airport to the destination airport, weather factors and delays for passengers with baggage.